Chylothorax in the context of alcoholic cirrhosis of the liver - Freitas, Ricardo (2008)
The authors present the case of a 70 year-old patient, with a story of chronic alcohol abuse and pulmonary tuberculosis in the past, admitted to hospital for pleural effusion. Physical examination showed jaundiced, decrease of breath sounds in the left hemithorax and abdominal prominence with flank tenderness. Abdominal ultrasound showed ascites and pleural effusion. Thoracocentesis revealed pleural fluid with characteristics of a transudative milky effusion. Liver biopsy showed a micronodular cirrhosis pattern. The option for Transjugular Intrahepatic Portosystemic Shunt (T.I.P.S.) resulted very well, and the patient remains clinically stable twelve months after its placement.